Strategi Pengembangan Objek Wisata Loko Tour dan Objek Wisata Geologi Sebagai Wisata Edukasi di Kabupaten Blora - Rony Ardian Putranto; Wiwik Widayati; Sulistyowati . (Journal of Politic and Government Studies, 2015)
This research aims to find out potential tourism objects which located in Blora, they are Loco Tour and Geology. Besides having a vacation there, visitors can also learn something new from each object there. Blora local Government doesn’t optimally mange these tourism objects yet, however these can be attraction to get people to come. These tourism objects are not well managed, and people don’t even realize the existence of these objects and. Therefore, this study aims to determine the best strategy in developing Blora local tourism objects, such as Loco Tour and Geological Tour as educational tours in Blora and determine government’s policy in developing tourism objects as educational tour in Blora.In this research, the researcher used qualitative approach to describe the result at the end of the research. The research was conducted in Blora, Central of Java. The data was gathered from recorded interviews and literature review. The head of Department of Transportation Tourism Culture Communication and Information Blora, was interviewed as the key informant. And the others were the employee of Loco Tour and Geology Tour, local people, and also the visitors who came to the objects as well. For the documented data, it was gathered from private documentation which took around the objects.Strategy in developing the Loco Tour and Geology as an educational tourism object in Blora based on the analysis result of SWOT has been formulated in several aspects such as exploiting educational potential on Loco Tour and Geology tourism objects, promoting educational tour, increasing awareness of local people to participate, giving information to local people about educational tourism developing program, optimizing the role of Kelompok Sadar Wisata (POKDARWIS), improving coordination among agencies in the development of educational tours, recruiting the capable employees, creating the local rules of tourism. Whereas Government policies are providing and developing facilities, increasing the human resources, promoting educational tour, and improving inter-institutional performance.